Systematic revision of the Plectopylinae (Gastropoda, Pulmonata, Plectopylidae) - Páll-Gergely, Barna (European Journal of Taxonomy, 2018)
The family Plectopylidae is divided into two subfamilies: Sinicolinae subfam. nov. (included extant genera: Gudeodiscus Páll-Gergely, 2013, Endothyrella Zilch, 1959, Halongella Páll-Gergely, 2015, Sicradiscus Páll-Gergely, 2013, Sinicola Gude, 1899) and Plectopylinae Möllendorff, 1898 (included genera: Chersaecia Gude, 1899, Hunyadiscus Páll-Gergely, 2016, Naggsia Páll-Gergely & Muratov, 2016, Plectopylis Benson, 1860). The Eocene fossil Plectopyloides Yen, 1969 is classified into the Sinicolinae. The Plectopylinae are revised mainly based on historical type and non-type material, and the material of the Florida Museum of Natural History, collected in Thailand in the 1980s. The following species-group taxa are described as new: Chersaecia auffenbergi sp. nov., Chersaecia densegyrata sp. nov., Chersaecia mogokensis sp. nov., Chersaecia reversalis sp. nov., Chersaecia scabra sp. nov., Chersaecia shiroiensis subnagaensis subsp. nov., Hunyadiscus tigrina sp. nov., Naggsia oligogyra sp. nov., Plectopylis crassilabris sp. nov., Plectopylis malayana sp. nov. and Plectopylis thompsoni sp. nov. The genus Endoplon Gude, 1899 is treated as a synonym of Chersaecia. Consequently, the two species classified in Endoplon are members of Chersaecia: Chersaecia brachyplecta (Benson, 1863) comb. nov. and Chersaecia smithiana (Gude, 1897) comb. nov. The genus Plectopylis is redefined, and includes only species with fused anterior and posterior lamellae. Thus, the following species are moved from Plectopylis to Chersaecia: Chersaecia feddeni (Blanford, 1865) comb. nov., Chersaecia goniobathmos (Ehrmann, 1922) comb. nov., Chersaecia leucochila (Gude, 1897) comb. nov., Chersaecia magna (Gude, 1897) comb. nov. and Chersaecia woodthorpei (Gude, 1899) comb. nov. Altogether thirteen species and varieties are moved to the synonymy of valid species: Helix (Plectopylis) brachydiscus Godwin-Austen, 1879 syn. nov., Helix (Plectopylis) ponsonbyi Godwin-Austen, 1888 syn. nov., Plectopylis (Chersaecia) kengtungensis Gude, 1914 syn. nov., Plectopylis (Chersaecia) degerbolae Solem, 1966 syn. nov., Plectopylis lissochlamys Gude, 1897 syn. nov., Helix repercussa Gould, 1856 syn. nov., Plectopylis achatina var. obesa Gude, 1898 syn. nov., Plectopylis achatina var. infrafasciata Gude, 1898 syn. nov., Plectopylis achatina var. venusta Gude, 1898 syn. nov., Plectopylis achatina var. castanea Gude, 1898 syn. nov., Plectopylis achatina var. breviplica Gude, 1898 syn. nov., Plectopylis achatina var. repercussoides Gude, 1899 syn. nov., Plectopylis linterae var. fusca Gude, 1898 syn. nov. Plectopylis (Chersaecia) simplex Solem, 1966 is a subspecies of Chersaecia perarcta (Blanford, 1865), whereas Plectopylis muspratti Gude, 1897 is a subspecies of Chersaecia nagaensis (Godwin-Austen, 1875).